[tex]poziom\ A\\\\I)\\\\7\frac{1}{3} +(-6 \frac{2}{3}) =7\frac{1}{3}-6\frac{2}{3}=6\frac{4}{3}-6\frac{2}{3}=\frac{2}{3}\\\\J)\\\\-5,11+(-3,45)=-5,11-3,45=-8,56\\\\K)\\\\-2\frac{5}{6} +(-1 \frac{5}{6})=-2\frac{5}{6} -1 \frac{5}{6}=-3\frac{10}{6}=-4\frac{4}{6}=-4\frac{2}{3}[/tex]
[tex]L)\\\\4,2+(-7,8)=4,2-7,8=-3,6[/tex]
[tex]Poziom\ B\\\\I)\\\\8 \frac{1}{3}-(-4 \frac{2}{3})=8\frac{1}{3}+4\frac{2}{3}=12\frac{3}{3}=13\\\\J)\\\\-5,11-3,45=-8,56\\\\K)\\\\2 \frac{5}{6}-7\frac{5}{6}=-5[/tex]
[tex]L)\\\\-4,2-(-7,8)=-4,2+7,8=3,6[/tex]